Somatic Praxis of Dynamic Postural Reorganization in Investigative Approaches of the Scenic Body - Domenici, Eloisa Leite (Revista Brasileira de Estudos da Presença, 2025)
This article discusses the contribution of Dynamic Postural Reorganization (DPR) to the scenic body from the perspective of theater and dance artists. The study develops a dialogic approach to this somatic technique and shows how, in their perception, sensorimotor and affective-cognitive propositions promote sensory refinement, scenic presence, and the activation of states of awareness. Special emphasis is placed on the work with slow tension, the technique’s main strategy, which, in addition to expanding tonic and expressive resources, facilitates the transit between the scenic material and the somatic work. The issue of autonomy in the relationship with somatic techniques and practices is revisited to conclude that this is a hallmark of DPR, reaffirming its potential to generate individual and collective agency, with strong applicability to the investigation of the scenic body.